Gap junctions between regulatory T cells and dendritic cells prevent sensitization of CD8+ T cells - Ring, Sabine; Karakhanova, Svetlana; Johnson, Theron S.; Enk, Alexander; Mahnke, Karsten (The journal of allergy and clinical immunology, 2010)
Background - Regulatory T (Treg) cells suppress the sensitization phase of experimental contact hypersensitivity (CHS) reactions when injected before hapten application. - Objective - Our aim was to analyze the mechanisms by which Treg cells suppress the sensitization phase of CHS reactions. - Methods - Treg cells were labeled with different fluorescent dyes and injected into naive mice directly before sensitization with the hapten 2,4,6-trinitro-1-chlorobenzene. Two days after sensitization, the lymphoid organs were analyzed for the presence of Treg cells and engagement of gap junctions with other cells. Dendritic cells (DCs) and effector CD8+T cells were isolated from the draining lymph nodes (LNs) of the differently treated groups, analyzed by using FACS for activation markers, and assessed for the T-cell stimulatory capacity of the DCs and the priming of effector T cells. - Results - Only the LN-homing Treg cells suppressed the sensitization phase in CHS reactions by means of establishing gap junctions with DCs in the dLNs. This gap junctional intercellular communication led to downregulation of T-cell costimulatory molecules on the surface of the DCs, abrogating the priming, activation, and proliferation of hapten-specific CD8+T cells. Consequently, the ear-swelling response induced by challenge with the respective hapten was prevented. - Conclusion - Treg cells not only modulate ongoing CD4+T cell-mediated immune reactions at tissue sites but also abrogate the de novo induction of CD8+T cell-driven immune reactions by interfering with T-cell stimulatory activity of DCs through gap junctional intercellular communication.